UNIVERSAL MAP OF INTERMITTENCY - Zhanabaev, Z.Zh.; Akhtanov, S.N. (Recent Contributions to Physics, 2017)
From the condition of fractal measures obtained universal map that describes its intermitted evolution with “accumulation - ejection” type. In contrast to all known differential and discrete models of dynamical systems this map realizes chaotic oscillations with characteristics that match criteria’s of self-organization.